Walk the line: a systemic perspective on stress experienced by emergency medical personnel by comparing military and civilian prehospital settings - Van Puyvelde, Martine; Van Herck, Jolien; Van den Bossche, Jeroen; Goethals, Frederic; Gijbels, Daisy; Detaille, Frederic; Pattyn, Nathalie (Frontiers in Public Health, 2023)
In the current study, we aimed at comparing civilian and military prehospital settings in emergency medicine (EM), in order to understand the type of stress events personnel experience; whether experience differs between civilian and military personnel; and how they cope with it. We used a mixed method approach, combining the results of a quantitative questionnaire and a thematic analysis of 23 in-depth semi-structured interviews to gain additional qualitative information. Whereas the questionnaire pointed to a significant preference for task-oriented coping over avoidant and emotion-oriented coping, the interviews offered a more nuanced insight, showing that EM personnel is continuously searching to position themselves on a continuum between emotional disconnection from the patient to preserve operationality on the one hand; and remaining enough empathic to preserve humanity on the other hand. We further identified an ambivalent awareness regarding emotions and stress; and a vulnerable disbalance between an excessive passion for the job with the sacrifice of own’s personal life (for a growing volatile and dangerous working environment) and a lack of recognition from both the patient and organizational environment. The combination of these factors may carry the risk for moral injury and compassion fatigue. Therefore, a mutual cycle of trust between the organizational level and EM personnel as well as among team members is crucial. The results showed high correspondence with the SHELL model indicating how the specific profile of EM personnel relates to the software, hardware, environmental and liveware components of their professional and private life. Trainings on stress- and risk awareness should be approached both on an individual and systemic level, knowing that there is clearly no “one-size-fits-all” manner.